PERAN TAMAN BACAAN MASYARAKAT PAGUYUBAN PEMUDA LITERASI GLOBAL (TBM PPLG) TERHADAP MINAT BACA ANAK USIA SEKOLAH DASAR - Haerotun Nufus; M. Taufik; Istinganatul Ngulwiyah; Sundawati Tisnasari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the role of the Global Literacy Youth Association Community Reading Park (TBM PPLG) on elementary school students’ reading interest in the academic year 2021-2022. The research conducted was qualitative descriptive research and the subjects involved students of elementary school at TBM PPLG. The data were collected through observation, interviews, and documentation. The data were analyzed by using data reduction, data presentation, and conclusion. The results indicated that 1) PPLG TBM encouraged elementary school students’ reading, 2) diverse reading materials, facilities, supporting infrastructure and interesting programs have been able to encourage public interest in reading, especially elementary school-aged children, and was supported by the parents’ role in fostering reading interest in elementary school-age children by getting used to reading books at home. Subsequently, the suggestions for PPLG TBM management and volunteers were expected to be able to give the time to participate in every PPLG TBM activity. It is used for optimizing and maximizing either students’ reading interest at the elementary school level or TBM PPLG inhabitances. To solve illiteracy for elementary school-aged students and TBM PPLG inhabitances, it is required to pay more attention and provide specifically study rooms for children who could not read. It is to optimize the teaching process and the need for teaching and learning methods regarding early reading, for example, by teaching the method of reading each syllable at the beginning of learning, the word method, the SAS method (Structural, Analytical, Synthetic), and the Sentence or Global Method (Syntaxis Method).